Penggunaan Media Audio Visual dalam Meningkatkan Hasil Belajar Siswa Memahami Materi Iman kepada Hari Akhir di Kelas IX SMPIT Insan Harapan - Lestari, Andini; Wahyudin, Undang Ruslan; Mustofa, Taufik (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
The purpose of Classroom Action Research (CAR) using audio-visual media for this learning is to increase the activity and learning outcomes of PAI (Islamic Religious Education) about the End of Days for Class IX students of SMP. The time of the study was in November 2019. The subjects of this study were Class IXB students in Semester 1 of the 2019/2020 academic year which consisted of 35 children. The data in this study are learning activities and learning outcomes. Data collection tools using observation sheets and written tests. The research procedure uses a Cycle Model which consists of 4 stages, namely Planning, Action, Observation, and Reflection. The results of this study are (1) learning becomes concrete and interesting; (2) students learn actively and effectively by listening, seeing, analyzing, taking notes, doing individual assignments, asking questions and giving opinions; and (3) students achieving better learning outcomes by increasing average scores and completeness. In the initial conditions, learning completeness is only 28.6%. in this cycle the completeness reached 83.9%. The suggestion is that the teacher: (1) give individual assignments to students to answer questions in writing after watching the film so that students are not only interested in the appearance of the film, but actually observe and analyze the content of the film; (2) paying attention to the content of the film, taking notes and asking questions, so that mastery of the material is increasing; and (3) optimizing the function of the audio-visual room and the completeness of the facilities available as interesting and effective learning media, so that learning is more meaningful.